First description of the environmental niche of the epibenthic dinoflagellate species Coolia palmyrensis, C. malayensis, and C. tropicalis (Dinophyceae) from Eastern Australia. Issue 3 (22nd February 2019) - Larsson, Michaela E.; Smith, Kirsty F.; Doblin, Martina A.
Abstract : Environmental variables such as temperature, salinity, and irradiance are significant drivers of microalgal growth and distribution. Therefore, understanding how these variables influence fitness of potentially toxic microalgal species is particularly important. In this study, strains of the potentially harmful epibenthic dinoflagellate species Coolia palmyrensis, C. malayensis, and C. tropicalis were isolated from coastal shallow water habitats on the east coast of Australia and identified using the D1‐D3 region of the large subunit (LSU) ribosomal DNA (rDNA). To determine the environmental niche of each taxon, growth was measured across a gradient of temperature (15–30°C), salinity (20–38), and irradiance (10–200 μmol photons · m −2 · s −1 ). Specific growth rates of Coolia tropicalis were highest under warm temperatures (27°C), low salinities (ca. 23), and intermediate irradiance levels (150 μmol photons · m −2 · s −1 ), while C. malayensis showed the highest growth at moderate temperatures (24°C) and irradiance levels (150 μmol photons · m −2 · s −1 ) and growth rates were consistent across the range of salinity levels tested (20–38). Coolia palmyrensis had the highest growth rate of all species tested and favored moderate temperatures (24°C), oceanic salinity (35), and high irradiance (>200 μmol photons · m −2 · s −1 ). This is the first study to characterize the environmental niche of species from the benthic harmful algal bloom genus Coolia and provides important information to help define species distributions and inform risk management.